IMPLEMENTASI STRATEGI PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMP N 2 MADANG SUKU I (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low level of students’ interest in learning Islamic Education (PAI), which is largely influenced by the dominance of conventional, teacher-centered teaching methods. The objective of this research is to examine the planning, implementation, and evaluation of interactive learning strategies in improving students’ learning interest at SMP Negeri 2 Madang Suku I. This research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of the implementation of interactive learning strategies. The findings reveal that the planning process was conducted systematically through the preparation of teaching modules and learning objectives tailored to students’ characteristics. The implementation of interactive learning strategies was carried out in three stages: introduction, core activities, and closing. During the core activities, teachers applied various methods such as group discussions, question and answer sessions, and educational games, which successfully encouraged students’ active participation and created a more engaging learning environment. The evaluation was conducted comprehensively by assessing both the learning process and outcomes through observation, tests, and assignments. The results indicate that interactive learning strategies effectively enhance students’ learning interest, as shown by increased participation, attention, enthusiasm, and confidence in expressing ideas. Therefore, interactive learning strategies are proven to be effective in improving the quality of PAI learning